The factors that influenced the success of women entrepreneurs during the COVID-19 in Kelantan / Nurul Diyanah Jamaluddin and Muhammad Hazim Zulkeplee - Jamaluddin, Nurul Diyanah; Zulkeplee, Muhammad Hazim (2022)
During this era, we had seen that there are many women who had ventured into the entrepreneurship fields as one of their sources of income for their lives. However, women in the entrepreneurship fields are not something unique to the society. This is because women had started venturing into entrepreneurship for a long period of time. Therefore, the purpose of the study is to find out and identify the factors of women entrepreneurs’ success during Covid-19 situations in Kelantan. Kelantan had known that there are many women that had been actively involved in the businesses since the mid-19th century. So, the study wants to know how they can be successful while struggling with the Covid-19 situation. In this study, we had been used quantitative approaches which using Google Forms as a medium to distribute our questionnaire. There are 212 respondents that had collected for our primary data and had been analysed to get our findings result between the dependent variable and independent variables. At the end of the study, it shows that there were only two factors shows the positive relationship to the women entrepreneurs’ success during Covid-19 in Kelantan, which are family support and creativity and innovation.